Early Detection of Periodontitis in Public Health Centres in Malang: An Overview - Nurma Azuro, Hanum; Yunus, Moch; Warih Gayatri, Rara (KnE Life Sciences, 2021)
Based on the Basic Health Research (Riskesdas) 2018, the incidence of periodontitis in Indonesia was reported at 74.1%, which makes it one of the most common oral health problems in the country. Overall, 2,759 patients, aged 19–64 years underwent periodontal examinations at the Public Health Centres in Malang between January and September 2019. The present study aimed to determine the description of periodontitis patients at the Public Health Centres, Malang, by conducting an early detection of periodontitis against the risk of the disease. This study used a cross-sectional design and a proportional random sampling technique. In total, 277 respondents visited the Public Health Centres in Malang during the study period. The early detection result is based on the number of questionnaire scores on signs, symptoms, and exposures to risk factors for periodontitis, which are divided into three categories: high, moderate, and low risks. The instrument used in this study is a modification of the previous research instrument by Renatus. The result showed that 58 respondents had moderate (21%), 4 (1.4%) had high, and 215 (77.6%) had low risks of periodontitis. Respondents who had a lower risk of periodontitis were more than the respondents who had high and moderate risks of periodontitis. Keywords: periodontitis, history of gingivitis, heredity (family history), oral hygiene, history of tobacco use